Transient Response of a Projectile in Gun Launch Simulation Using Lagrangian and Ale Methods - A Tabiei; M Chowdhury; N Aquelet; M Souli (International Journal of Multiphysics, 2016)
This paper describes the usefulness of Lagrangian and arbitrary Lagrangian/Eulerian (ALE) methods in simulating the gun launch dynamics of a generic artillery component subjected to launch simulation in an air gun test. Lagrangian and ALE methods are used to simulate the impact mitigation environment in which the kinetic energy of a projectile is absorbed by the crushing of aluminum honeycomb mitigator. In order to solve the problem due to high impact penetration, a new fluid structure coupling algorithm is developed and implemented in LS-DYNA, a three dimensional FEM code. The fluid structure coupling algorithm used in this paper combined with ALE formulation for the aluminum honeycomb mitigator allows to solve problems for which the contact algorithm in the Lagrangian calculation fails due to high mesh distortion. The numerical method used for the fluid and fluid structure coupling is discussed. A new coupling method is used in order to prevent mesh distortion. Issues related to the effectiveness of these methods in simulating a high degree of distortion of Aluminum honeycomb mitigator with the commonly used material models (metallic honeycomb and crushable foam) are discussed. Both computational methods lead to the same prediction for the deceleration of the test projectile and are able to simulate the behavior of the projectile. Good agreement between the test results and the predicted projectile response is achieved via the presented models and the methods employed.